Drivers of FDI in Fast Growing Developing Countries: Evidence from Bundling and Unbundling Governance - Simplice A. Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2015)
We assess drivers of FDI in a panel of BRICS and MINT countries for the period 2001-2011. We bundle and unbundle governance determinants using a battery of contemporary and non-contemporary estimation techniques. The following findings are established. First, for both contemporary and non-contemporary specifications, while determinants for gross FDI are significant, they are not for net FDI. Second, for contemporary specifications, the significance of the governance dynamics is as follows in increasing order of magnitude: general governance, political governance, economic governance, political stability, regulation quality and government effectiveness. The motivation to bundle governance variables is articulated by the effect of political governance. Third, for non-contemporary specifications, the significance of governance variables is as follows in ascending order of magnitude: economic governance, institutional governance, general governance, corruption-control, political governance and political stability. The importance of combining governance indicators is captured by the effects of political governance, economic governance and institutional governance. The results indicate that the simultaneous implementation of the various components of governance clarifies a country's attractiveness for FDI location. Policy implications are discussed with particular emphasis on the timing of FDI and its targeting.
Keywords: C52; F21; F23; P37; P39; 330; Foreign direct investment; emerging countries; governance